Ocular biometric indices in Vietnamese 46 to 65 years of age - Hien Thi Thu Nguyen; Khoa Xuan Ngo; Luan Thanh Nguyen; Luong Van Hoang (Revista Cubana de Medicina Militar)
Introduction: Ocular axial length, anterior chamber depth and central corneal thickness are three important ocular biometric indices. These measurements are useful to show changes in the Vietnamese population with presbyopia. Objectives: To determine the ocular biometric indices, ocular axial length, anterior chamber depth and central corneal thickness, in Vietnamese population and evaluate the correlation between these indices. Methods: A cross-sectional study was carried out in a Vietnamese population, aged 46 to 65 years. Data on ocular axial length, anterior chamber depth and central corneal thickness were collected. The Student's t test and ANOVA were used to compare the means of the indices, grouped by age and sex. The relationship between the ocular biometric indices was tested using Pearson's correlation, with a significance level of p <0.05. Results: 390 eyes of 195 people were analyzed. The mean length of the ocular axis was 23.13 ± 0.66 mm, the depth of the anterior chamber, 3.15 ± 0.36 mm, and the central corneal thickness, 529.15 ± 30.57 µm. The three biometric indices decreased with age and were higher in men (p <0.05). The length of the ocular axis had a positive relationship with the depth of the anterior chamber (r = 0.411 and p <0.001) and the central corneal thickness (r = 0.141 and p <0.001). There was no relationship between anterior chamber depth and central corneal thickness (r = 0.039 and p = 0.44). Conclusion: Three ocular biometric indices decreased with age and were higher in men. The length of the ocular axis was related to the depth of the anterior chamber and the thickness of the central cornea.